Quality of instructional materials in Nigerian university distance learning programmes (2010)
The increasing demand for placement in tertiary institutions, without commensurate increase in intakes has necessitated a paradigm shift to open/distance learning programmes. These programmes are characterized by learner-centredness, independent learning and recognition of prior learning. The modes of instructions of distance learning are peculiar with accompanying challenges. This study, therefore, examined the quality of instructional materials in the universities of lbadan and Lagos Distance Learning Programmes comparatively. The Input- Process-Output evaluation model was employed with emphasis on the input aspect to guide the study. Samples of 400 participants (400 learners from both programmes) were proportionally selected. Two research questions guided the study. One validated instrument was used to collect data. Data were analyzed using frequency counts, percentages and mean. The University of Ibadan Distance Learning Centre (UIDLC) had more textual materials (84.3%) than University of Lagos Distance learning Institute (ULDLI)'s (70.8%), while audio-visual materials and internet facilities were in short supply in both programmes. The two distance learning institutions were striving to meet the stated objectives of using global quality modes of instruction in educating distance learners and utilising innovative method of programme delivery. The two institutions must aim at improving teaching-learning resources, staff capacity development, learner support services, provide students with adequate accessibility to facilities such as e-library, ICT's, internet facilities, and collaborate with reputableforeign distance learning institutions in order to position distance education in Nigeria for global competitiveness.